Enhancing chemical delivery efficiency through sett treatment device for management of red rot in sugarcane (Saccharum officinarum) - MD MINNATULLAH; AJEET KUMAR; R VISWANATHAN; SUNITA KUMARI MEENA; SUDHIR PASWAN; PIYUSH KUMAR (The Indian Journal of Agricultural Sciences)
The management of red rot in sugarcane (Saccharum officinarum L.) poses a significant challenge to growers due to its detrimental effects on yield and quality. The present study was carried out during 2021–22 and 2022–23 at Kalyanpur farm, Sugarcane Research Institute, Dr. Rajendra Prasad Central Agricultural University, Pusa, Samastipur, Bihar aimed to enhance the efficiency of chemical for managing red rot through sett treatment device (STD) in sugarcane (varieties CoSe 95422 and CoV 92102). Treatments, viz. T1, Sett treatment in STD with Thiophanate Methyl (Roko 70 wp) at 1.3 g/L; T2, T1 + soil drenching with Thiophanate Methyl at 1.3 g/L on the 45th and 90th days; T3, Sett treatment in STD with Carbendazim (50 wp) at 1.0 g/L; T4, T3 + soil drenching with Carbendazim at 1.0 g/L on the 45th and 90th days; T5, Sett treatment with Carbendazim 50 wp at 1.0 g/L + Urea at 0.5 g/L, ZnSO4 at 0.5 g/L + FeSO4 at 0.5 g/L + Fipronil (5 sc) at 0.5 ml/L + Soil drenching by 30th and 45th days with Carbendazim 50 ml @1.0 g/L; T6, Healthy setts resistant control; T7, Infected setts + Grain inoculation (Untreated disease control) were applied to single-budded setts. Results demonstrated a significant reduction in disease incidence and settling mortality, along with improved quantitative and qualitative cane parameters compared to untreated controls. The combination of Carbendazim 50 wp, Urea, ZnSO₄, FeSO₄ and Fipronil, with additional soil drenching, yielded the highest germination rates (70.38% in CoSe 95422 and 65.30% in CoV 92102). CoSe 95422 exhibited superior performance in cane length (256.67 cm), girth (7.98 cm), yield (87.42 t/ha) and sucrose content (16.94%). Similarly, CoV 92102 achieved substantial gains, including a yield of 84.95 t/ha and sucrose content of 16.10%. Correlation analysis revealed strong positive associations between germination percentage, cane yield and quality parameters (brix, sucrose and purity), while disease incidence and settling mortality negatively impacted these metrics. The integration of fungicides, insecticides and micronutrients through mechanized delivery significantly enhanced sugarcane productivity and quality, emphasizing the role of micronutrients in addressing deficiencies in subtropical soils.